Edukasi Konsep Dasar Nilai Tukar Petani dalam Mendukung Hasil Jual Produksi Petani guna Meningkatkan Pendapatan dan Kesejahteraan Petani Padi di Desa Medan Krio - Anggia Ramadhan; Radiyan Rahim; Nurul Nabila Utami (Arsil Media, 2024)
The purpose of community service is to provide an understanding of the exchange value for farmers in supporting the sale of agricultural products to increase the income and well-being of rice farmers in Medan Krio Village, Deli Serdang Regency. The specific target of this community service is to ensure that rice farmers in Medan Krio Village understand the concept of exchange value in supporting the sale of production and can improve the production and well-being of rice farmers in Medan Krio Village. The content presented in this community service includes the basic concept of exchange value and how it supports the sale of production, aiming to enhance the income and well-being of rice farmers in Medan Krio Village. The outcome of this community service indicates that rice farmers in Medan Krio Village are now aware of and understand the basic concept of the exchange value for farmers in supporting the sale of agricultural products to increase income and well-being.